Reputation reform strategies in local government: investigating Denmark and Norway. Issue 4 (4th July 2019) - Lockert, Åshild Skjegstad; Bjørnå, Hilde; Haugen, Kristian H.; Salomonsen, Heidi Houlberg
ABSTRACT: This article investigates reputation reform in Norwegian and Danish local government and whether they have the same strategy content depending on the degree of administrative involvement and municipality size. Political and administrative actors are likely to cultivate different types of reputation strategies (place or organisational reputation), which explicitly embrace the potentially diverging interests cultivated by the two types of actors. We use a comparative design and quantitative method with an empirical ambition to explore local government reputation strategies in two national contexts. We find that local government responses to reputation reform depend on the size of the municipality and the type of actors involved; the larger the municipality, the more the administration is involved. And the more that administrative actors are involved, the more the strategies target organisational reputation. The country-specific factors do not appear to be the most important determinants for reputation reform strategies.